In-depth haemodynamic phenotyping of pulmonary hypertension due to left heart disease. Issue 5 (24th May 2018) - Gerges, Christian; Gerges, Mario; Fesler, Pierre; Pistritto, Anna Maria; Konowitz, Nicholas P.; Jakowitsch, Johannes; Celermajer, David S.; Lang, Irene M.
The commonest cause of pulmonary hypertension (PH) is left heart disease (LHD). The current classification system for definitions of PH-LHD is under review. We therefore performed prospective in-depth invasive haemodynamic phenotyping in order to assess the site of increased pulmonary vascular resistance (PVR) in PH-LHD subsets. Based on pulmonary artery occlusion waveforms yielding an estimate of the effective capillary pressure, we partitioned PVR in larger arterial ( R up, upstream resistance) and small arterial plus venous components ( R ds, downstream resistance). In the case of small vessel disease, R up decreases and R ds increases. Inhaled nitric oxide (NO) testing was used to assess acute vasoreactivity. Right ventricular afterload (PVR, pulmonary arterial compliance and effective arterial elastance) was significantly higher in combined post- and pre-capillary PH (Cpc-PH, n=35) than in isolated post-capillary PH (Ipc-PH, n=20). Right ventricular afterload decreased during inhalation of NO in Cpc-PH and idiopathic pulmonary arterial hypertension (n=31), but remained unchanged in Ipc-PH. R up was similar in Cpc-PH (66.8±10.8%) and idiopathic pulmonary arterial hypertension (65.0±12.2%; p=0.530) suggesting small vessel disease, but significantly higher in Ipc-PH (96.5±4.5%; p<0.001) suggesting upstream transmission of elevated left atrial pressure. Right ventricular afterload is driven by elevated left atrial pressure in Ipc-PH and is further increased by elevated small vessel resistance in Cpc-PH. Cpc-PH is responsive to inhaled NO. Our data support current definitions of PH-LHD subsets. Combined post- and pre-capillary PH is characterised by pre-capillary pulmonary vascular disease and a positive response to inhaled NO http://ow.ly/G2nF30iYTeJ